Enhancing Large Group Nature Tour Experiences : A Study of Taiga Times - Saks, Reti-Liis (2023)
The aim of this thesis is to provide Taiga Times with a comprehensive overview of the factors that are key to creating a successful and memorable nature tour experience for large customer groups. The objective of this thesis is to ascertain the key elements and attributes of Taiga Times' existing tour offerings that have contributed to their success, with a specific focus on their applicability and potential integration into the framework of large group tours. The information base has been gathered by focusing on different subsections of tourism, such as cultural tourism, nature tourism, experiential tourism, and sustainable tourism, as well as knowledge of tourism products and the development of new products. This thesis followed a service design process called design thinking, which includes five main steps. During the first phase of ‘discovery’ an interview with Taiga Times CEO took place. The second phase of ‘conception’ included discourse analysis of pre-existing customer feedback; benchmarking similar companies and a brainstorming session. The third and fourth phases of ‘designing’ and ‘building’ were used to detail the final list of consideration while utilising the Experience Triangle method. The last phase of ‘implementation’ is for Taiga Times to carry out. The key findings from the interview process included Taiga Times being committed to providing a personal traveling experience to their customers, how sustainability plays a large role in their overall operation and what their existing large group tours entail. The discourse analysis section identified customer needs as well as best practices. The benchmarking process viewed tourism businesses providing similar products and provided valuable information on understanding the customer experience. The brainstorming process provided a comprehensive overview of challenges as well as creative solutions. The final results include a variety of factors which influence the experience based on individuality, authenticity, storytelling, multisensory, contrast, ...